Genetic diversity and mutual relationships through principal component analysis in F2 generation of aus rice (Oryza sativa L.): Principal component analysis in aus rice - Sarna, SG; Waza, Showkat A; Aminul Islam, AKM (ORYZA-An International Journal of Rice, 2025)
The present study was carried out to enumerate the extent of genetic diversity for yield components in 15 different F2 segregating populations with their 10 parents of Aus rice using principal component analysis (PCA), clustering and linkage analysis. In the correlation matrix, 14 characters of 25 genotypes generated14 principal components without changing their relative positions and the first four PCs explained 42.1%, 15.5%, 12.2% and 7.5% of total variation towards genetic diversity. In two cluster condition, 25 genotypes were grouped into two clusters having 7 genotypes (P2 x P1, P2 x P5, P2 x P6, P1, P2, P8, P10) in cluster 1 and 18 genotypes cluster 2. In the three cluster condition, there were 4, 6, 15 individuals in cluster 1, 2 and 3, respectively. In four cluster condition, clusters consisted of 4, 14, 3, 4 genotypes, respectively. Cluster means for the days to maturity, number of non-effective tillers per plant, empty grains per plant showed the lowest values in cluster 1. On the other hand, number of tillers per plant, effective tillers per plant, panicle length, filled grains per panicle, grain length and thousand seed weight showed maximum cluster means in cluster 4. The dendrogram revealed that six genotypes (P8 x P3, P7, P3, P7 x P3, P3 x P4, P11) having more distance as compared to rest (19 genotypes) of the genotypes. In complete linkage, 25 genotypes were grouped into two major clusters. Cluster 1 containing seven genotypes and cluster 2 containing 18 genotypes; among the two clusters, there was maximum cluster distance than the sub-clusters. Cluster 1 showed two sub clusters where four genotypes (P1, P2 x P1, P2 x P5, P2) were in one cluster and three genotypes (P11, P8 and P10) in another cluster. Cluster 2 also contains two sub-clusters in which three genotypes remain in one sub-cluster and 15 genotypes in another sub-cluster. In average linkage, 25 genotypes were also grouped into two major clusters. The first cluster contains three genotypes (P7, P3 x P4, P7 x P3) and the second cluster divided into two sub-clusters which contain rest of the genotypes (22 genotypes). It can be concluded that, there were more distance where cluster number was less and the distance was less where the cluster number was more.